PEMANFAATAN MEDIA LOOSE PARTS DALAM IMPLEMENTASI KURIKULUM MERDEKA UNTUK MENGEMBANGKAN KREATIVITAS ANAK USIA DINI: STUDI PUSTAKA - Inneke Octafia Utami; Novi Pardarina; Gustia Haryati (LPPM IAD Probolinggo, 2026)
The implementation of the Merdeka Curriculum in early childhood education emphasizes child-centered, contextual, and creativity-oriented learning. One learning medium that supports this approach is loose parts, which consist of open-ended materials that encourage children to explore, imagine, and solve problems independently. This study aims to analyze the role of loose parts in implementing the Merdeka Curriculum to foster creativity in early childhood through a literature review. Data were collected from national and international scientific articles published between 2023 and 2026, as well as relevant theoretical sources. Data were analyzed using content analysis through data reduction, data display, and conclusion drawing. The findings indicate that loose parts possess open-ended characteristics that enable children to explore various ideas, enhance divergent thinking, problem-solving skills, collaboration, communication, and creativity. Furthermore, loose parts are aligned with the principles of differentiated learning in the Merdeka Curriculum, allowing children to learn according to their interests, needs, and developmental stages. The successful implementation of loose parts depends on teachers' competencies in designing learning environments, conducting authentic assessment, and collaborating with parents. Therefore, loose parts serve as an effective learning strategy to support creativity development in early childhood within the implementation of the Merdeka Curriculum.